AfSIS Diagnostic Trials Project - Kihara, Job Maguta (2012)
The Africa Soil Information Service (AfSIS) is a large-scale research-based project, which develops detailed digital soil maps using new types of soil analysis and statistical methods. One AfSIS objective is to develop site-specific management recommendations. This AfSIS Diagnostic Trials Project website describes the methods and tools developed for this purpose, from field trial and experiment design and implementation to data analysis and interpretation.